Metagenome Sequences of Sediment from a Recovering Industrialized Appalachian River in West Virginia - Huber, David H. (Genome Announc, 2018)
We sequenced two metagenomes from upper sediment layers (0 to 5 and 6 to 10 cm) from the Kanawha River, West Virginia. The watershed includes inputs from the forested Appalachian Mountains, surface coal mining, municipal residues, and extensive chemical manufacturing. The dominant bacterial phyla were Proteobacteria, Bacteriodetes, Firmicutes, Actinobacteria, and Chloroflexi. Xenobiotic degradation pathways were present.